The Several Factors That Can affect the growth of Manufacturing Company Profits listed on the Indonesia Stock Exchange for the period 2016-2018 - F Firdaus, Venus; Masruhin, Masruhin (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study aims to examine the effect of profitability, capital structure, operating cash flow and firm size on earnings growth. The population of this study is all manufacturing companies listed on the Indonesia Stock exchange (IDX) in 2016-2018. Based on purposive sampling method, the total sample of this study was 19 companies. The analysis carried out in this research is descriptive statistical test, panel data testing, classical assumption test and hypothesis test. The measurement tool used for this analysis is the Eviews 9. The result of this study indicate that based on the partial test (t test) profitability, operating cash flow and firm size have a positive effect on earnings growth while capital structure has a negative effect on earnings growth. Taken together (test f) profitability, capital structure, operating cash flow and firm size affect the earnings growth